2000
DOI: 10.1074/jbc.275.18.13812
|View full text |Cite
|
Sign up to set email alerts
|

Activated 3′,5′-Cyclic AMP-dependent Protein Kinase Is Sufficient to Induce Neuroendocrine-like Differentiation of the LNCaP Prostate Tumor Cell Line

Abstract: Neuroendocrine (NE) differentiation within prostate tumors is proposed to be a contributing factor in disease progression. However, the cellular origin and molecular mechanism controlling differentiation of prostatic NE cells are unresolved. The prostate tumor cell line, LNCaP, can reversibly acquire many NE characteristics in response to treatment with ␤-adrenergic receptor agonists and activators of adenylate cyclase. In this study, we demonstrate that these treatments induce protein kinase A (PKA) activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 31 publications
(31 reference statements)
1
100
0
4
Order By: Relevance
“…We and others have previously shown that LNCaP cells undergo NE-like differentiation following treatment with epinephrine, forskolin or interleukin-6 (Qiu et al, 1998;Cox et al, 1999Cox et al, , 2000Deeble et al, 2001) and demonstrated that expression of a constitutively active form of the PKA catalytic subunit, Cqr, in LNCaP cells results in the acquisition of NE characteristics (Cox et al, 2000). These NE-like cells secrete significantly greater amounts of NT and PTHrP than undifferentiated LNCaP cells .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…We and others have previously shown that LNCaP cells undergo NE-like differentiation following treatment with epinephrine, forskolin or interleukin-6 (Qiu et al, 1998;Cox et al, 1999Cox et al, , 2000Deeble et al, 2001) and demonstrated that expression of a constitutively active form of the PKA catalytic subunit, Cqr, in LNCaP cells results in the acquisition of NE characteristics (Cox et al, 2000). These NE-like cells secrete significantly greater amounts of NT and PTHrP than undifferentiated LNCaP cells .…”
Section: Resultsmentioning
confidence: 79%
“…LNCaP cells acquire NE characteristics in response to androgen withdrawal, IL-6 addition and/or treatment with physiological and pharmacological agents that elevate intracellular cyclic adenosine monophosphate (cAMP), such as epinephrine, isoproterenol, forskolin and dibutyryl cAMP (Qiu et al, 1998;Cox et al, 1999Cox et al, , 2000Deeble et al, 2001). Removal of differentiating agents results in reversion to the tumor cell phenotype, indicating that the process is reversible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that LNCaP cells could be induced to undergo transdifferentiation to a neuroendocrine (NE)-like morphology by increases in intracellular cyclic AMP, 13 growth in steroid-depleted media, 14 or by treatment with interleukin-6. 15 We sought to mimic androgen ablation in LNCaP cells to address what changes would occur in Bcl-2 and Bax.…”
Section: Growth Of Lncap Cells In Charcoal-stripped Media or Casodex mentioning
confidence: 99%
“…Although it is well established that the activation of Erk kinases is regulated by receptor tyrosine kinases such as EGFR and platelet-derived growth factor receptor (PDGFR) via activation of Ras, which in turn activates the Raf-1/Mek/Erk1/2 cascade (Hagemann and Blank, 2001;Johnson and Lapadat, 2002), more recently, adrenergic receptor (AR) stimulation of cAMP has also been shown to regulate the activation of Erk1/2 in normal cells (reviewed in Carman and Benovic, 1998;Cox et al, 2000;Enserink et al, 2002;Stork and Schmitt, 2002). For example, in some normal cells such as cardiac myocytes and bone cells, cAMP was shown to activate Erk1/2, whereas in others such as adipocytes and endothelial cells, it was shown to inhibit Erk1/2 activation (Vossler et al, 1997;Steinberg, 2000;Stork, 2001, 2002;Troadec et al, 2002).…”
Section: Introductionmentioning
confidence: 99%